Multiculturalidade e colaboração crítica entre surdos e ouvintes na visão de um pesquisador tradutor-intérprete de libras/português - Oliveira, Everton Pessôa de (2016)
This research aims at examining the existing multicultural contradictions in the relations among deaf and hearing people from Digit-M-Ed São Paulo Project. In the core of the investigation, it also aims at confronting the way the concepts of multiculturalism (MOREIRA; CANDAU, 2011; ROJO, 2012; SANTOS, 2010) and critical collaboration (MAGALHÃES, 2010) are inserted in the research environment and how researchers, coordinators, students and, specially, Portuguese - Sign Language translators and interpreters contribute in the deaf – listeners relation in order to foster transformations in the discursive practices of the research participants. The production of this essay is justified by the introduction of different ways of reflecting about deaf and listener’s teaching-learning process in shared spaces. This study’s theoretical framework is founded on the Socio-Historical-Cultural Activity Theory (VYGOTSKY, 1930/1999; 1934/2008); LEONTIEV, 1977; ENGESTRÖM, 1987; LIBERALI, 2009) and on the multiculturalism and argumentation concepts (LIBERALI, 2013). It also presents Vygotsky’s concepts on the human development and how they are connected with the deaf. In methodological terms, it is organized as a Critical Collaborative Research (MAGALHÃES, 2004, 2007, 2009), which focus is on the subject and on its own action in development, with the purpose to observe the contexts and interfere on them in an attempt to cause transformations. Data was produced in meetings of Digit-M-Ed São Paulo Project, organized by the research group Language in Activities in School Contexts (LACE) from Pontifícia Universidade Católica de São Paulo (PUC-SP). Deaf and listener participation mediated by Portuguese - Sign Language translators and interpreters, who are also participants of the research, had been observed. This survey analysis point out to multicultural aspects and indicate that communicational barriers can be transcended through critical collaboration among deaf participants, Portuguese - Sign Language translators and interpreters and listeners